Serology and protein electrophoresis for evidence of exposure to 12 mink pathogens in free-ranging American mink (Neovison vison) in Argentina - Martino, Pablo Eduardo (2017)
Background: Basic pathologic characteristics for farmed minks were previously reportedworldwide. However, its status in the wild has not been studied in detail. Also, there is a lack ofsystematic investigations from South America.Objective: Serology and electrophoresis were carried out for evidence of exposure to 12 minkpathogens on two different locations.Animals and methods: Serology was done in 87 wild minks by reference techniques againstToxoplasma gondii, Encephalitozoon cuniculi, Neospora caninum, Brucella abortus, Mycobacteriumbovis, Leptospira interrogans, canine distemper virus (CDV), canine adenovirus (CAV), canineparvovirus (CPV), rabies virus (RV), Influenza A virus (FLUAV) and Aleutian disease virus (ADV). Forthe detection of hypergammaglobulinemia (the Aleutian disease main clinical feature),gammaglobulin concentrations were determined by conventional electrophoresis.Results: Seventy-one percent of the 87 sera had antibodies against one or more pathogens.ADV accounted for the highest seroprevalence (29%), followed by T. gondii (26%), L. interrogans(14%), M. bovis (12%), B. abortus (9%), N. caninum (3%), CPV (3%) and CDV (2%). Seroprevalencewas influenced by location but not sex or age. Additionally, 16% of the seropositive samples forADV had gammaglobulin levels >20% of the total protein concentration. Antibody titers forCDV and CPV were low and difficult to interpret as almost all these cases had borderlineconcentrations.Conclusion: A cautious interpretation of the results is urged as the epidemiological role ofthe wild mink is largely unexplored for most of these agents. Nevertheless, the informationmay be clinically relevant and may stimulate conservation organizations to supportQ4 research programs.